(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The present article contains basic information about the emergence of a new language science field of linguistic culture, which reflects the system of linguistic norms, the sum of the people’s behavior and nationality and the directions of development of its schools. Language is a reflection of culture.